W poszukiwaniu sensu śmierci dziecka. Z perspektywy chrześcijańskiej - Bartoszek, Antoni (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2012)
Death is an unusual mystery and the death of a child is an especially unusual mystery. Such death violates the natural chronology of events as it makes someone completely innocent and defenseless pass away and deeply affects family relationships. This article does not have the ambition to unravel the great mystery of human existence, but it only attempts to deal with some of its aspects at the philosophical and theological level. It points out that there is no simple relationship between the death of a child anda moral life, especially that of parents’. To look for such a relationship as a justifi cation of a child’s death would be unfair. When it comes to relationships with God, on the one hand, the death of a child may cause parents to remove God from their lives and even to deny His existence; on the other hand, an attempt to accept the death of a child may be understood as a sacrifi ce offered to God. Such death becomes a privileged space for experiencing the profound effects of God’s grace and mercy, and it brings about a deeply human attitude, first, to a dying child, and then to those who have been left with a void after their child’s death. In this way, it deepens interpersonal relationships.